The view from Rainshadow Bay - Coble, Colleen (Nashville, Tennessee : Thomas Nelson, 2018)
"Her photographs capture the beauty of Puget Sound. Do they also expose a darkness that someone would kill to keep buried? After her husband, Jack, dies in a climbing incident, Shauna has only her five-year-old son and her helicopter charter business to live for. Every day is a struggle to make ends meet and she lives in constant fear of losing even more than she already has. When her business partner is murdered, his final words convince Shauna that she's in danger too. But where can she turn? Zach Bannister was her husband's best friend and is the person she blames for his death. She's barely spoken to him since. But right now he seems her only hope for protecting her son. Zach is only too happy to assuage his guilt over Jack's death by helping Shauna any way he can. But there are secrets involved dating back to Shauna's childhood that more than one person would prefer to stay hidden. In The View from Rainshadow Bay, suspense, danger, and a longing to love again ignite amid the gorgeous lavender fields of Washington State"--
"From USA TODAY bestselling author Colleen Coble comes a news series set amid the gorgeous lavender fields of Washington state--but the beauty masks deadly secrets"--
Includes discussion questions.
Keywords: Mothers and sons -- Fiction; Widows -- Fiction; Suspense fiction; Christian fiction; Mystery fiction